2009
DOI: 10.1061/(asce)te.1943-5436.0000009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cyclic Triaxial Behavior of Unbound Granular Material under Constant and Variable Confining Pressure

Abstract: Cyclic stresses due to passing wheels impose an accumulation of permanent strains in layers of unbound granular materials (UGMs) of flexible pavements. The hollow cylinder triaxial test would be the most appropriate test to simulate the in situ stress conditions but it is difficult to perform on UGMs due to their large maximum grain size. The simpler axi-symmetric cyclic triaxial test does not consider the shear stress components. It can be performed with a constant (CCP) or a variable confining pressure (VCP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…For example, based on many totally-drained tests on sands, Wichtmann et al [35] observed approximately double accumulation rates of permanent axial strain under certain stress paths with variable confining pressure, compared to the stress paths with constant confining pressure (CCP tests); Rondon et al [27] compared the drained behavior of unbound granular materials under several stress paths with and without cyclic confining pressure, and their results show that the conventional cyclic triaxial tests with constant confining pressure may underestimate the settlement induced by traffic loading in some cases. All these studies proved that the variable confining pressure plays an important role in the deformation behavior of soils, especially when drainage is allowed.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…For example, based on many totally-drained tests on sands, Wichtmann et al [35] observed approximately double accumulation rates of permanent axial strain under certain stress paths with variable confining pressure, compared to the stress paths with constant confining pressure (CCP tests); Rondon et al [27] compared the drained behavior of unbound granular materials under several stress paths with and without cyclic confining pressure, and their results show that the conventional cyclic triaxial tests with constant confining pressure may underestimate the settlement induced by traffic loading in some cases. All these studies proved that the variable confining pressure plays an important role in the deformation behavior of soils, especially when drainage is allowed.…”
Section: Introductionmentioning
confidence: 98%
“…For the simulation of traffic loading, compressive cyclic deviatoric stress cycles have been proved to be insufficient by many researchers (Powrie et al [24]; Yang [25]; Grabe [26]; Rondon et al [27]; Cai et al [23]). As shown in Fig.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…[7,20]), non-destructive in-situ investigations and correlations with empirical parameters (e.g. [6,14]) were proposed to measure the resilient modulus of unbound granular materials.…”
Section: Unbound Granular Materials -Nonlinear Elastic Models Considementioning
confidence: 99%